Inequality, finance and renewable energy consumption in Sub-Saharan Africa - Simplice Asongu; Nicholas M. Odhiambo (African Governance and Development Institute (AGDI), 2020)
The study investigates linkages between financial development, income inequality and renewable energy consumption from 39 countries in Sub-Saharan Africa. The empirical evidence is based on data for the period 2004-2014, Generalized Method of Moments (GMM) and Quantile Regressions (QR). The GMM results show that financial development unconditionally promotes renewable energy consumption while income inequality counteracts the underlying positive effect. The QR results reveal that the GMM findings only withstand empirical validity in bottom quantiles of the renewable energy consumption distribution. In order to increase room for policy implications for the promotion of renewable energy consumption, critical masses of income inequality that should not be exceeded are computed for bottom quantiles of the renewable energy consumption distribution while income inequality thresholds that should be exceeded are computed for top quantiles of the renewable energy consumption distribution. The study reconciles two strands of the literature. Theoretical, practical and policy implications are discussed.
Keywords: H10; Q20; Q30; O11; O55; 330; Renewable energy; Inequality; Finance; Sub-Saharan Africa; Sustainable development